Clinical Significance of Impacted Supernumerary Teeth of a Group of Sri Lankan Children Aged 7 to 13 Years - Herath, E. M. U. C. K.; Premathilaka, L. K. N.; Perera, K.; Jayawardena, J. A. C. K. (The Journal of Dentists, 2018)
Aim: The objective of this study was to investigate the characteristics of impacted supernumerary teeth (SNT) and their sequalae in a group of Sri Lankan children. Methods: Data were collected from the archives of patient’s records and radiographs. Descriptive analysis was made from data using Minitab Statistical Software. Results: A total number of 58 impacted SNT were found in 49 children. The mean age of the sample was 9.89 ± 2.01 years and male to female ratio was 2.77: 1. Out of 49 subjects 81.6% had one impacted supernumerary tooth and 18.4% had two. The majority of the children with impacted SNT were in the age range of 8-10 years (44.9%) followed by 11-13 years (40.82%) and 5-7 years (14.28%). While 57 (98.3%) SNT were identified in the region of premaxilla only one was seen in the canine region. The commonest shape was conical (63.8%), followed by tuberculate (20.75%), odontomes (12.1%) and supplemental (3.4%) respectively. Regarding the direction of impaction of SNT, many (48.3%) were inverted followed by vertical orientation (37.9%) and other directions (13.78%). The common sequalae associated with impacted SNT were delayed eruption of the permanent teeth (46.55%) and malocclusion (20.68%). There were considerable numbers of cases without any clinical effects (29.31%) at the time of presentation to the clinic. Vertically oriented SNT caused more clinical problems (72.72%) than the inverted impacted SNT (64.28%). Conclusion: SNT were more prevalent among males (M:F = 2.77:1) than females and were mostly diagnosed in the age range between 8 - 13 years. DPT (Dental Panaromic Tomogram) radiological investigation is suggested when the patient presents with one SNT as there is a tendency for paired supernumeraries.